2017
DOI: 10.1038/srep39776
|View full text |Cite
|
Sign up to set email alerts
|

U24 from Roseolovirus interacts strongly with Nedd4 WW Domains

Abstract: U24 is a protein found in both roseoloviruses Human Herpes Virus type 6 and 7 (HHV-6 and HHV-7), with an N-terminus that is rich in prolines (PY motif in both HHV-6A and 7; PxxP motif in HHV-6A). Previous work has shown that the interaction between U24 and WW domains is important for endocytic recycling of T-cell receptors, but a cognate ligand was never identified. In this contribution, data was obtained from pull-downs, ITC, NMR and molecular dynamics simulations to show that a specific interaction exists be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The PY motif of U24 is able to associate with Itch (Fig. 3 ) and the WW domain of Nedd4 25 . As the PY motif of U24 is responsible for CD3ε down-regulation, we examined whether this function is conserved among all viral proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PY motif of U24 is able to associate with Itch (Fig. 3 ) and the WW domain of Nedd4 25 . As the PY motif of U24 is responsible for CD3ε down-regulation, we examined whether this function is conserved among all viral proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Sang et al . reported that the PY motifs of U24 proteins are able to interact with the WW domains of Nedd4 proteins in an acellular system 25 . In addition, the m42 gene product of mouse cytomegalovirus (MCMV), a homolog of HCMV UL42, down-regulates CD45 expression on the MCMV-infected macrophage surface and induces the lysosomal degradation of CD45 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The roseoloviral protein U24 is a C-tail-anchored membrane protein shown to affect recycling and endocytosis of cell-surface receptors (131,132). In addition, U24 function may be linked to MS, as it has been found to mimic the interaction of myelin basic protein's function with its binding partner Fyn (133,134). The N-terminal region of U24 encoded by HHV-6A and HHV-7 contains a PPxY motif that was shown to interact with HECTfamily E3 ligases SMURF2 and Nedd4, albeit more strongly with WW domain 3 of Nedd4 (135).…”
Section: Epstein-barr Virus (Ebv; Human Gammaherpesvirus 4)-mentioning
confidence: 99%
“…Importantly, because sodium channels have been found to be associated with MS lesions, investigators speculated that U24 may interfere with the endosomal recycling of sodium channels known to be regulated by Nedd4. Although still speculative, results from Sang et al (133) suggest that the PPxY motif of U24 and its strong interaction with WW domain 3 of Nedd4 may play a role in MS or other related demyelinating diseases.…”
Section: Epstein-barr Virus (Ebv; Human Gammaherpesvirus 4)-mentioning
confidence: 99%
“…However, in immunocompromised individuals, HHV-6B reactivation can be problematic and occasionally life-threatening (5),(6),(7). In case of HHV-6A, several reports have associated the virus with neurodegenerative diseases such as multiple sclerosis and more recently with Alzheimer’s disease (8), (9), (10), (11). In spite of their pathological differences, both HHV-6A and HHV6B can readily integrate their genomes into host chromosomes (12), (13), (14).…”
Section: Introductionmentioning
confidence: 99%